Use of agrowaste as soilless medium for Molineria latifolia var. Megacarpa (Lemba) and Rhodomyrtus tomentosa (Aiton) Hassk. (Kemunting) in urban landscape - Baharudin, Sarah (2015)
Tremendous amount of biomass waste leads to waste disposal problems and environmental problems. Therefore, it is necessary to carry out research to obtain substantial data with regards to growing ornamental plants in this new combination of soilless media compared to normal topsoil and other soil-based mixtures. Most ornamental plants are exotic or imported species. Large numbers of native and local plants species in Malaysia are still under-utilized as landscape and ornamental plants. There is a need to reintroduce the species to nursery industry. Soilless media can be used to evaluate growth and establishment of native ornamental plants. The present study was conducted to investigate the effects of agrowaste in soilless growing medium on growth and flowering of 2 local species of ornamentals: Molineria latifolia var. Megacarpa (lemba) and Rhodomyrtus tomentosa (kemunting) for urban landscape use. The first objective was to formulate suitable light weight soilless media using locally available renewable resources such as oil palm waste compost as the main component and cocopeat, vermiculite, biochar (charred rice husk and empty fruit bunch) and sewage sludge as additives. Secondly, to determine the effects of selected soilless media formulations on growth and flowering performances of the species. Thirdly, to determine public preferences on the species grown in soilless media as potential landscape plants for the future. The study recommended two soilless formulations for the species. 90% EFB Compost + 10% rice-husk biochar (10 CRH) to be used to grow Molineria latifolia var. Megacarpa and 90% EFB Compost + 10% EFB biochar (10 EBC) to grow Rhodomyrtus tomentosa. Both media are recyclable, low-cost, readily available, easy to handle, lightweight and produce uniform plant growth thus making it a preferable planting medium. The study can also be concluded that the two native test plants have high potentials to become urban landscape plants of the future.